2009
DOI: 10.1590/s1807-59322009000800016
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Blood Substitutes: Examining The History, Clinical Trial Results, and Ethics of Hemoglobin-Based Oxygen Carriers

Abstract: The complications associated with acquiring and storing whole blood for transfusions have launched substantial efforts to develop a blood substitute. The history of these efforts involves a complicated mixture of science, ethics, and business. This review focuses on clinical trials of the three hemoglobin-based oxygen carriers (HBOC) that have progressed to Phase II or III clinical trials: He-mAssist (Baxter; Deerfield, IL, US), PolyHeme (Northfield; Evanston, IL, US), and Hemopure (Biopure; Cambridge, MA, US)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(138 citation statements)
references
References 36 publications
1
134
0
3
Order By: Relevance
“…This is a lower oxygen affinity than that of native RBCs. It also has an increased molecular weight, with an average of 250 kDa (Range: 130-500) (36). There are a number of parallels between these products.…”
Section: Chemical Approaches That Deal With Hboc-induced Vasoconstricmentioning
confidence: 99%
“…This is a lower oxygen affinity than that of native RBCs. It also has an increased molecular weight, with an average of 250 kDa (Range: 130-500) (36). There are a number of parallels between these products.…”
Section: Chemical Approaches That Deal With Hboc-induced Vasoconstricmentioning
confidence: 99%
“…1 Blood substitutes have to overcome the acute renal toxicity associated with the delivery of free hemoglobin in the circulatory system and to prevent fast clearance from the bloodstream, vasoconstriction, and severe cardiac effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid clearance from the bloodstream of the carrier, its degradation leading to the release of free hemoglobin, or the uncontrolled change of the oxygen-binding properties of hemoglobin impairing its oxygen delivery efficiency have limited their clinical application. 1,5,12 In their meta-analysis of 16 clinical trials of hemoglobin-based blood substitutes, Natanson and coworkers concluded that the use of HBOCs is associated with a significant increase of the risk for myocardial infarction and death. 2 The development of HemAssist was later abandoned by Baxter, and the clinical trial of Hemopure on trauma patients in the United States was halted by the US Food and Drug Adminsitration.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin-based artificial oxygen carriers (HBOCs), which include cross-linked (Chen et al, 2009), polymerized (Jahr et al, 2008), and polymer-conjugated Hb (Smani, 2008), have been developed to overcome problems associated with blood transfusion, such as crossmatching, blood-bone infections (human immunodeficiency virus and hepatitis virus), and the shortage of donated blood. Several of these HBOCs are currently in the final stages of clinical evaluation.…”
Section: Introductionmentioning
confidence: 99%